Implementation Of Legal Protection Of Occupational Safety And Occupational Health At Pt Tiga Serangkai Pustaka Mandiri - Rizka; Mawaddah Nur Amini (IHSA Institute, 2022)
Implementation of the legal protection of occupational safety and health at PT Tiga SerangkaiPustaka Mandiri thus contains how the company implements occupational safety and healthprograms for workers, which has regulated UU No 13 of 2003 concerning Ketenagakerjaan. In addition, it includes what obstacles exist and the efforts made. The empirical research method describes the facts in the field and gets maximum results from interviews and fieldobservations. The proceed of the testing can be said that the application of legal protection ofwork safety and health of workers at PT Tiga Serangkai hasn't been fully implementedcorrectly, that had been carried out properly are implementing appropriate working hours, then the existence of BPJS Ketenagakerjaan which guarantees health insurance for workers. Then there are obstacles, namely the lack of incomplete warning signs on the available places andmachines. That can trigger work accidents for workers.